Diagnostic accuracy of combined pleural fluid adenosine deaminase and lymphocyte-to-neutrophil ratio versus CBNAAT/TrueNat in suspected tubercular pleural effusion patients - Indraneel Bose; Jaydip Deb; Shilpi Adhikary; Dibyendu Saha (The Journal of Association of Chest Physicians, 2025)
Background: Although rapid cartridge- and chip-based assays such as CBNAAT and TrueNat provide precise and timely diagnosis of tubercular pleural effusion, their sensitivity in immunocompetent individuals remains lower than that of other pleural fluid markers. In a high-tuberculosis (TB)-prevalence regions, markedly elevated pleural fluid adenosine deaminase (ADA) combined with strong clinical suspicion can justify treatment initiation. In low-prevalence areas, ADA retains a high negative predictive value (NPV) but its positive predictive value declines. By contrast, the combined use of pleural fluid ADA and the lymphocyte-to-neutrophil ratio markedly improves sensitivity, specificity, positive predictive value and NPV for TB detection compared with either method alone. Aim: This 23-month longitudinal comparative study assessed the diagnostic performance—sensitivity, specificity, positive predictive value and NPV —of pleural fluid nucleic acid amplification tests alone versus pleural fluid ADA levels combined with lymphocyte-to-neutrophil ratio. Materials and Methods: Adult patients with either microbiologically confirmed pulmonary TB with pleural effusion or histopathologically confirmed tubercular granuloma on pleural biopsy were enrolled at a tertiary care hospital in Eastern India. Participants had no significant comorbidities. Institutional ethical committee approval was obtained prior to study initiation. Statistical analysis used the following: data were entered into Microsoft Excel and analysed using SPSS version 27.0 (SPSS Inc., Chicago, IL, USA) and GraphPad Prism version 5. Results: CBNAAT and TrueNat positivity rates were 54.5%, a nonsignificant finding. Elevated pleural fluid ADA (>45 U/L) was observed in 23 patients (69.7%; significant). Lymphocyte-to-neutrophil ratios were 0.50–0.60 in 14 patients (42.4%), 0.61–0.75 in 14 (42.4%) and >0.75 in 5 (15.2%); these distributions reached statistical significance.